Mason-Pfizer Monkey Virus Envelope Glycoprotein Cycling and Its Vesicular Co-Transport with Immature Particles - Prokšová, Petra Grznárová; Lipov, Jan; Zelenka, Jaroslav; Hunter, Eric; Langerová, Hana; Rumlová, Michaela; Ruml, Tomáš (Viruses, 2018)
The envelope glycoprotein (Env) plays a crucial role in the retroviral life cycle by mediating primary interactions with the host cell. As described previously and expanded on in this paper, Env mediates the trafficking of immature Mason-Pfizer monkey virus (M-PMV) particles to the plasma membrane (PM). Using a panel of labeled RabGTPases as endosomal markers, we identified Env mostly in Rab7a- and Rab9a-positive endosomes. Based on an analysis of the transport of recombinant fluorescently labeled M-PMV Gag and Env proteins, we propose a putative mechanism of the intracellular trafficking of M-PMV Env and immature particles. According to this model, a portion of Env is targeted from the trans-Golgi network (TGN) to Rab7a-positive endosomes. It is then transported to Rab9a-positive endosomes and back to the TGN. It is at the Rab9a vesicles where the immature particles may anchor to the membranes of the Env-containing vesicles, preventing Env recycling to the TGN. These Gag-associated vesicles are then transported to the plasma membrane.
Keywords: endosomes; transportní vezikuly; intracellular trafficking; virus-like particles; Virus Assembly; Endosomes; Simian Acquired Immunodeficiency Syndrome; Cell Membrane; Animals; AIDS opičí; Gene Products, env; zvířata; endozomy; envelope; buněčná membrána; Transport Vesicles; Protein Transport; Masonův-Pfizerův opičí virus; Mason-Pfizer monkey virus; transport; transport proteinů; genové produkty env; sestavení viru